Pozzolanic Activity of Fly Ash - Farooque, KN; Yeasmin, Z; Alam, S; Alam, AMS; Zaman, M (Bangladesh Journal of Scientific and Industrial Research, 2011)
Various physico-chemical properties such as particle size distribution, specific gravity, specific surface area, chemical composition, solubility of Fly Ash (FA) in NaOH and pozzolanic activity of fly ash towards lime have been investigated. Chemical analysis of FAreveals that the FA used in this present investigation belongs to class F type of fly ash. XRD investigation of FA depicts the presence of crystalline mullite and quartz phases. Pozzolanic activity of fly ash was investigated by pH and electrical conductivity measurement, by determining the amount of calcium reacted with fly ash and by the amount of Insoluble Residue (IR) observed in FA-lime paste. XRD investigation of ash-lime paste identified the Calcium Silicate Hydrate (C-S-H) phase. The results obtained from these studies suggested that fly ash possesses pozzolanic activity. Key words: Pozzolanic activity; Fly ash (FA); Rice husk ash; Ordinary Portland Cement (OPC); Insoluble residue (IR); Calcium hydroxide (CH); Calcium silicate hydrate (C-S-H); Kinetics; XRD. DOI: 10.3329/bjsir.v45i4.7326 Bangladesh J. Sci. Ind. Res. 45(4), 303-308, 2010